#### Answer

3

#### Work Step by Step

From the table, we see that: $f(5)=6$ and $f(6)=3$, so we have:
$(f\circ f)(5)=f(f(5))=f(6)=3$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

3

From the table, we see that: $f(5)=6$ and $f(6)=3$, so we have:
$(f\circ f)(5)=f(f(5))=f(6)=3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.